A New Model of Economic Growth - Kaldor, Nicholas; Mirrlees, James A. (Review of Economic Studies, 1962)
Nicholas Kaldor, James A. Mirrlees; A New Model of Economic Growth, The Review of Economic Studies, Volume 29, Issue 3, 1 June 1962, Pages 174–192, https:/